A Survey of the Median Nerve Elasticity after Volar Locking Plate Fixation Using Ultrasound Elastography - Sugiyama, Yoichi; Naito, Kiyohito; Miyamoto, Hideaki; Goto, Kenji; Kinoshita, Mayuko; Nagura, Nana; Iwase, Yoshiyuki; Kaneko, Kazuo (Journal of Hand and Microsurgery, 2019)
Introduction Median nerve disorder is one of the complications after surgery using volar locking plate (VLP) for distal radius fracture (DRF). In this study, elasticity of the median nerve was quantified using ultrasound elastography (EG) (real-time tissue EG) and compared between the operation and healthy sides in patients after surgery for DRF using VLP.Materials and Methods The subjects of this study were 28 patients (4 males and 24 females; mean age: 58.5 years) who could be followed up for more than 6 months after surgery for DRF and were able to be examined by EG. We evaluated median nerve elasticities on the operation and healthy sides using EG on the final follow-up.Results The median nerve strain ratios were 3.97 ± 2.99 on the operation side and 3.91 ± 1.51 on the healthy side, showing no significant difference in elasticity of the median nerve between the operation and healthy sides.Conclusion Median nerve disorder, which is a complication after surgery with VLP, can be objectively detected using EG capable of evaluating median nerve elasticity externally to detect medial nerve degeneration while degeneration of the median nerve. Thus, EG may be used as a useful diagnostic tool to prevent complications and decide on appropriate timing of VLP extraction.
Keywords: elastography; distal radius fractures; median nerve; volar locking plate; complications; carpal tunnel syndrome